ANALISA MANAJERIAL SISTEM TERHADAP PRODUKTIFITAS KARYAWAN - Susi Handayani; Aidil Firmansyah (Universitas Indo Global Mandiri)
The study entitled Analysis of Leadership Style on Employee Performance At Sarana Karya Mandiri CV Palembang. Performance is the result of the work accomplished by individuals who disesuaikandengan role or duties associated with a measure of value tertentudari company where the individual works. The role of leadership style needed to perform functions within the organization in order to obtain maximum employee performance. Likewise, the formation of good norganisasi komitme expected to support and improve the performance of the maximum. Leaders with good leadership style will create high motivation within each subordinate, so the motivation will arise morale can improve the performance of subordinates. The aim of this study was to determine how much performance Leadership Style Analysis Employees At Sarana Karya Mandiri CV Palembang. Number of members of the population of 30 respondents. This research uses descriptive analysis with qualitative approach using questionnaires and documentation as a means of collecting data by using two variables, namely the style of leadership and employee performance. The lower the low style of leadership that is applied then semkain less motivated employees and vice versa. Results of this study stated that the influence of leadership style that is so big on employee performance in CV Sarana Karya Mandiri Palembang.Key words : Style of Leadership, Motivation and Performance